Establishment of a patient-derived orthotopic osteosarcoma mouse model - Blattmann, Claudia; Thiemann, Markus; Stenzinger, Albrecht; Roth, Eva Kathrin; Dittmar, Anne; Witt, Hendrik; Lehner, Burkhard; Renker, Eva Kristin; Jugold, Manfred; Eichwald, Viktoria; Weichert, Wilko; Huber, Peter E.; et al. (Journal of translational medicine, 2015)
Osteosarcoma (OS) is the most common pediatric primary malignant bone tumor. As the prognosis for patients following standard treatment did not improve for almost three decades, functional preclinical models that closely reflect important clinical cancer characteristics are urgently needed to develop and evaluate new treatment strategies. The objective of this study was to establish an orthotopic xenotransplanted mouse model using patient-derived tumor tissue.